Meaningful inclusion of people with dementia in interview research: adopting the “intentional stance” - O’Shea, Emma; Timmons, Suzanne; Irving, Kate (Frontiers in Dementia, 2025)
Engaging people living with dementia in interview research presents unique ethical, methodological, and practical challenges. In recent years there is an increased recognition of the importance and value of meaningfully including people with dementia in research, and of the epistemic injustice of systematic exclusion. While there are a growing number of research papers suggesting strategies for fostering ethical and meaningful inclusion, this area is still very much in development, theoretically and methodologically. This paper outlines how a theoretical perspective on selfhood in dementia, which incorporates the concept of the “Intentional Stance” (as per Sabat), may be a useful means of reaching people with dementia in a meaningful way via open, curious and personhood-supporting interactions. Embodying the “intentional stance” refers to operating under the assumption that all behavior and interactions do have meaning(s), even if it is not immediately or intuitively evident to the researcher what the meaning(s) are. Here, we draw on excerpts from an interview I conducted with a person living with dementia about his experiences of and perspectives on respite and day services, using the intentional stance, in conjunction with a range of other strategies for maximizing reciprocal communication. The analysis highlights instances where the intentional stance was central to connecting with the person, and temporarily entering their lifeworld. Adopting this stance is a means of reducing the epistemic injustice that people with dementia have faced, through longstanding omission and exclusion from research, and from social spheres more broadly.